Role of Galectin-3 in intervertebral disc degeneration: an experimental study - Jianjiang Li; Nianrong Han; Zhenqiang Liu; Akram Osman; Leilei Xu; Jing Song; Yang Xiao; Wei Hu (BMC Musculoskeletal Disorders, 2024)
Abstract Background This study investigated the role of Galectin-3 in the degeneration of intervertebral disc cartilage. Methods The patients who underwent lumbar spine surgery due to degenerative disc disease were recruited and divided into Modic I, Modic II, and Modic III; groups. HE staining was used to detect the pathological changes in endplates. The changes of Galectin-3, MMP3, Aggrecan, CCL3, and Col II were detected by immunohistochemistry, RT-PCR, and Western blot. MTT and flow cytometry were used to detect cartilage endplate cell proliferation, cell cycle, and apoptosis. Results With the progression of degeneration (from Modic I to III), the chondrocytes and density of the cartilage endplate of the intervertebral disc decreased, and the collagen arrangement of the cartilage endplate of the intervertebral disc was broken and calcified. Meanwhile, the expressions of Aggrecan, Col II, Galectin-3, Aggrecan, and CCL3 gradually decreased. After treatment with Galectin-3 inhibitor GB1107, the proliferation of rat cartilage end plate cells was significantly reduced (P < 0.05). GB1107 (25 µmol/L) also significantly promoted the apoptosis of cartilage endplate cells (P < 0.05). Moreover, the percentage of cartilage endplate cells in the G1 phase was significantly higher, while that in the G2 and S phases was significantly lower (P < 0.05). Additionally, the mRNA and protein expression levels of MMP3, CCL3, and Aggrecan in rat cartilage end plate cells were lower than those in the control group. Conclusions Galectin-3 decreases with the progression of the cartilage endplate degeneration of the intervertebral disc. Galectin-3 may affect intervertebral disc degeneration by regulating the degradation of the extracellular matrix.